Economic policy uncertainty and executive turnover - Hong Huang; Haiyu Liu; Baohua Yang (China Journal of Accounting Research, 2020)
This paper examines whether economic uncertainty increases executive turnover. The negative perception perspective and business change theory suggest that executives are more likely to leave their jobs during periods of corporate distress. However, the additive effects of internal and external risk are thought to prompt firms to carefully consider executive turnover, thereby reducing the likelihood of executive changes. Based on the literature, we propose a check-and-balance hypothesis for the relationship between external uncertainty and executive change, according to which the optimal superposition of the internal and external risks stemming from increased external uncertainty would be to avoid a wave of executive departures. Using a sample of Chinese A-share listed companies from 2010 to 2019 and the China economic policy uncertainty index of Baker et al. (2013), we examine the impact of economic policy uncertainty on executive turnover and our results support the check-and-balance hypothesis. Our findings enhance our understanding of how economic policy uncertainty affects executive turnover, and enrich the literature on corporate risk management and strategic management.
Keywords: 650; Economic policy uncertainty; Executive turnover; Risk taking; Director-manager duality